State Bar Annual Meeting in Monterey - Watkins, Howard::::::::: (1988)
Fresno attorneys informal time in hotel room: Standing: Robert Oliver, Brad Hill, ?, John Missirlian, G. Dana French; Seated: Sandra Snyder, Linda Fischbach, Debra Kazanjian, Karen Burt, and Thomas Tusan